Peningkatan Kemampuan Bicara pada Anak Speech Delay dengan Metode Bercerita di Tk Negeri 1 Muara Ancalong - Melya Wati; Atien Nur Chamidah (Jurnal Ners, 2026)
This study aims to improve speaking skills in children with speech delay disorders through the application of storytelling methods in TK Negeri 1 Muara Ancalong. This study uses a Classroom Action Research (CAR) approach implemented in two cycles. Each cycle consists of four stages, namely planning, action implementation, observation, and reflection. The research subjects were group A children aged 4–5 years who experienced speech delay. Data collection techniques used observation, interviews, and documentation, while data analysis was carried out by calculating the average and percentage of children's learning completion. The results of the study showed an increase in children's speaking skills from cycle I with an average completion of 66% (sufficient category) to 83% in cycle II (good category). This 17% increase indicates that the storytelling method is effective in developing children's expressive language skills, enriching vocabulary, and increasing children's courage to speak in front of teachers and friends. Thus, the storytelling method can be used as a creative and fun learning strategy in stimulating the speaking skills of early childhood, especially for children with speech delay, so that their language development can develop optimally.